Pengaruh Penerapan Kurikulum Merdeka terhadap Hasil Belajar Siswa Mapel PAI Kelas VII SMPN I Kabuh Jombang - Aisah, Nia Nur; Waslah, Waslah; Huda, Saihul Atho Alaul (Lembaga Yasin AlSys, 2025)
The curriculum in an education is an important thing in the process of learning in schools, if a school does not have a curriculum in learning it will not run according to the goals to be achieved. This research aims to find out the significant influence of the application of the Independent Curriculum on student learning outcomes in PAI subjects. This research method is a quantitative study and uses random sampling techniques, sampling in this study totals 67 respondents. The data collection technique in this study uses the questionnaire method. The results of the research that has been conducted using spss 30 show that the hypothesis test in the study using the moment product correlation analysis test with the result of the significance value of the data test is 0.605 greater than the rtable (0.605 < 0.244), and in the test using the T test, the results are obtained Based on the T test, it shows that the regression coefficient of the variable Implementation of the Independent Curriculum 0.001 < 0.05. then it can be concluded that Ha is accepted and H0 is rejected which means that there is a significant influence between the application of the Merdeka curriculum on student learning outcomes.